Relative age effects in elite Chinese soccer players: Implications of the `one-child` policy - Li, Z.; Mao, L.; Steingröver, C.; Wattie, N.; Baker, J.; Schorer, J.; Helsen, W. F. (PLOS ONE, 2020)
The relative age effect (RAE) refers to the asymmetrical distribution of birthdates in a cohort found in many achievement domains, particularly in sports with many participants like soccer. Given the uniqueness of the one-child policy in China, this study examined the existence of the RAE in elite Chinese male and female soccer players generally and relative to their playing position on the field. Results showed a clear and obvious RAE for all age groups (U20 male, U18 male, adult female and U18 female) with the observed birthdate distributions for each age group significantly different from expected distributions (p<0.05). Additionally, we noticed a differential RAE according to the players` position on the field as reflected in different effect sizes. In male players, the RAE was significantly greater in Defenders (DF) and Goalkeepers (GK) compared to Midfielders (MF) and Forwards (FW) (VDF = 0.266>VGK = 0.215>VMF = 0.178>VFW = 0.175). In female players, GKs had a larger RAE (VGK = 0.184>0.17, VDF = 0.143, VMF = 0.127, VFW = 0.116). To reduce the negative consequences associated with RAEs throughout player development systems, potential solutions are discussed.